Investigation of the Reference Interval Values of Fasting Plasma Glucose, Blood Pressure, and Blood Lipids in the Longevity People Aged 90 Years Old and Above - Wang Z (Dove Medical Press, 2021)
Zhaoping Wang,1 Xiaolin Ni,1,2 Danni Gao,2,3 Liang Sun,1 Xiaoquan Zhu,1 Juan Jiao,4 Qi Zhou,1 Chen Chen,1 Nan Zhang,1 Zhu Wu,1 Ze Yang,1 Huiping Yuan1 1The MOH Key Laboratory of Geriatrics, Beijing Hospital, National Center of Gerontology, National Center for Gerontology, Beijing, 100730, People’s Republic of China; 2Graduate School of Chinese Academy of Medical Science and Peking Union Medical College, Beijing, 100730, People’s Republic of China; 3Peking University Fifth School of Clinical Medicine (Beijing Hospital), Beijing, 100730, People’s Republic of China; 4Clinical Laboratory Department, The Seventh Medical Center, PLA General Hospital, Beijing, 100730, People’s Republic of ChinaCorrespondence: Huiping YuanThe MOH Key Laboratory of Geriatrics, Beijing Hospital, National Center of Gerontology, Dongdan DaHua Road 1#, Beijing, 100730, People’s Republic of ChinaTel +86-10-58115043Fax +86-10-65237929Email yuanhuiping@126.comPurpose: To our knowledge, the normal fasting plasma glucose (FPG), blood pressure (BP), and blood lipids (BL) interval values have not been well-established in the longevity population. This study aims to provide a reference for the establishment of normal BP, FPG, and BL interval values in the longevity people in China.Patients and Methods: A total of 7417 people were selected from the natural longevity cohort in Guangxi, with an age range of 20– 110 years old, including 7093 classified as the non-longevity (20– 89 years old) (94.02%) and 324 classified as the longevity (≥ 90 years old) (5.98%); there were 4309 men (58.1%) and 3108 women (41.9%). FPG, systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), and low-density lipoprotein (LDL-C) levels were defined as desirable levels when they were below the 75th percentile (P75), borderline levels from the 75th to 90th percentile (P75–P90), and high levels above P90; triglyceride (TG) levels above P90 were defined as high; and high-density lipoprotein cholesterol (HDL-C) levels below the 5th percentile (P5) were defined as low levels.Results: The reference interval values of FPG in the longevity were as follows: desirable levels < 6.15 mmol/L, borderline levels 6.15– 7.45 mmol/L, high levels ≥ 7.45 mmol/L. Reference interval values of systolic blood pressure (SBP) were as follows: desirable levels < 160.00 mmHg, borderline levels 160.00– 174.50 mmHg, high levels ≥ 175.00 mmHg. DBP reference interval values were as follows: desirable levels < 88.00 mmHg, borderline levels 88.00– 90.00 mmHg, high levels ≥ 90.00 mmHg. TC reference interval values were as follows: desirable levels < 5.59 mmol/L, borderline levels 5.59– 6.45 mmol/L, high levels ≥ 6.45 mmol/L. LDL-C reference interval values were as follows: desirable levels < 3.30 mmol/L, borderline levels 3.30– 3.85 mmol/L, high levels ≥ 3.85 mmol/L. TG reference interval values were as follows: desirable levels < 2.82 mmol/L, high levels ≥ 2.82 mmol/L. HDL-C reference interval values were as follows: low levels < 0.80 mmol/L, desirable levels ≥ 0.80 mmol/L.Conclusion: The reference interval values of BP, FPG, and BL are different between the longevity population and the non-longevity population, and the interval values change with increasing age.Keywords: longevity, blood pressure, fasting plasma glucose, blood lipids, reference interval values